Strengthening MSME Financial Reports: The Influence of Accounting Knowledge and Education, Moderated by SAK EMKM Socialization - Erlina Widayanti Djatnicka; Dian Sulistyorini Wulandari; Mainatul Khasanah (PT. Banjarese Pacific Indonesia, 2024)
This study investigates the influence of Accounting Knowledge and Education on the quality of MSME financial reports, focusing on the moderating role of SAK EMKM Socialization (Indonesian Financial Accounting Standards for Micro, Small, and Medium Enterprises). Using survey data collected from MSME operators, the research reveals that accounting knowledge has a strong positive relationship with financial reporting quality. Education also plays a positive but weaker role, suggesting significant potential for improvement. The study finds that the socialization of SAK EMKM significantly improves the quality of MSME financial reports but does not moderate the relationship between either accounting knowledge or education and financial report quality. These findings suggest that education and accounting knowledge are fundamental in improving MSME financial reporting practices, while SAK EMKM socialization is more effective for MSMEs with limited financial literacy. This research highlights the need for tailored training programs and socialization efforts to address the specific needs of MSMEs, ensuring that all operators, regardless of educational background, can produce high-quality financial reports in line with established standards.